TYPES AND EFFECTS OF DOMESTIC VIOLENCE ON ADOLESCENTS IN BORNO STATE, NIGERIA - Ngohi Bukar Umar; Ibrahim Dahiru Idriss; Halliru Abdullahi Muhammad; Gambo Garba Muhammad; Jaafar Zubairu Maitama (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
A descriptive correlational study was used to determine the types and effects of domestic violence as well as the relationship between domestic violence and adolescentsâ€™ academic performance by gender in Borno State, Nigeria. The target population of the study comprised of 20,774 SS 11 students in public secondary schools, however, 300 subjects constituted the sample. A stratified random sampling technique was used in selecting the respondents based on gender, school location, and years of exposure to domestic violence. 155(51.67%) of the subjects were males while 145(48.33%) were females. Researchersâ€™ self-authored 36 item instrument tagged â€œDomestic Violence Questionnaire (DVQ)â€ was used to elicit data for the study. The instrument had a validity index of .83 and a Cronbach alpha reliability coefficient of .91. Four objectives, three research questions, and one null hypothesis piloted the study. Data collected were analyzed using mean, standard deviation, and t-test. The findings of the study identified slapping and suicidal ideation as some of the types of domestic violence. Some of the effects of domestic violence include downheartedness, trauma, and melancholy in Borno State. Thus, arresting the menace of domestic violence requires a multi-dimensional approach blending the positive actions of the government at all levels and counsellors among other stakeholders. Some counselling implications and recommendations were proffered.